If it's not what You are looking for type in the equation solver your own equation and let us solve it.
36-12x+3=x
We move all terms to the left:
36-12x+3-(x)=0
We add all the numbers together, and all the variables
-13x+39=0
We move all terms containing x to the left, all other terms to the right
-13x=-39
x=-39/-13
x=+3
| 7x-60=2x | | 3x(x+1)=2(x+11) | | 1=3/4h-8 | | 6+6+6=x | | 105x^2+96x-56=0 | | -4(3a=-7) | | 1x+1x+50=120 | | 9x—11-3x-13=0 | | -3(7n-4)=-36-5n | | 2z+8/3=(z/4)+5 | | .4x=-6.4 | | 6(x+3)-4=x+9-10 | | 12(x-3)+18=6(20-3) | | -5x+2=13x+-160 | | -2b+5=-2(b+2)+7 | | 2x+3x+5=5x+5 | | H+£=y | | -8x+12=-5(8x+4) | | 321321+344.5x=333.64 | | 1/2(3w-8)=25 | | 49=11-2(8+3x) | | 2x16=21-7 | | -81=-41-9n | | 3(x-5)-10=2x-17 | | 3x(5x÷30)×2=7x+60 | | –19j+8j+–4=18 | | 12=17-p | | .7x+.2(40)=0.5(x+20) | | 5y+2+2y+9=12y-9 | | 6(x-9)=6x | | -(x+3)+3x=2(x+3) | | 15x+9=-2x+128 |